Pengaruh Pemahaman Bahasa Arab terhadap IstinbÄá¹ Hukum Fikih - Ahmad Syaripudin; Sirajuddin, Sirajuddin; Rustam Efendi; Dedi Rochmad Hermawan Ali (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This research aims to find out the extent of the influence of understanding Arabic on istinbÄá¹ law of jurispruding. This research is qualitative descriptive research focused on the study of manuscripts and texts with a philosophical approach. The results showed that: first, Arabic has a massive urgency to the sciences of Sharia; Second, arabic has a significant impression of the determination of jurisprudence which is indicated by the disagreements that occur among fuqahÄ' in many problems of Islamic jurisprudence due to differences in viewpoints in understanding propositions based on dilÄlah al-alfaÅ¼.